Investigation of the interaction between phloretin and Staphylococcus aureus toxin proteins and its application in chicken meat - Hong Li; Ce Shi; Tariq Aziz; Nawal Al-Hoshani; Manal F. Elkhadragy; Abdelrahman R. Ahmed; Haiying Cui; Lin Lin (Food Chemistry, 2026)

Correction: The potent human CAR activator CITCO is a non-genotoxic hepatic tumour-promoting agent in humanised constitutive androstane receptor mice but not in wild-type animals - C. J. Henderson; A. W. McLaren; A. K. MacLeod; D. Lin; A. R. Cameron; L. R. Chatham; J. Moggs; F. Inesta‑Vaquera; John P. Thomson; Richard R. Meehan; P. Chakravarty; M. Schwarz; et al. (Archives of Toxicology, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Plasticity and regional heterothermy of upper thermal tolerance in the ring-necked snake - Christian L. Cox; Kelly Lin Wuthrich; Dareen Aloudeh; Samuel J. Baker; Anna G. Climo; Alexa F. Gross; Christian W. Kizer; Zoe M. Korff; Oscar Melendez Vera; Veronica Y. Silva; Alexis M. Spans; Grace R. Thilenius; et al. (Journal of Thermal Biology, 2026)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

P20-17 Polyethylene terephthalate (PET) nanoplastics induce acute pulmonary inflammation in mice - Ø.P. Haugen; L.M.A. Camassa; H.F. Berntsen; F.-C. Lin; V. Alcolea-Rodriguez; R. Portela; F. Barbero; O.A.H. Foss; H. Sadeghiankaffash; Ø. Skare; S. Alsaedi; A.L. Moen; et al. (Toxicology Letters, 2025)

Removal of PFAS and pharmaceuticals from municipal wastewater using a novel β-cyclodextrin adsorbent over distinct contact times - Emma F. Shapiro; Zhi-Wei Lin; Edwin Saavedra Cifuentes; Francisco J. Barajas-Rodriguez; Rosa Gwinn; William R. Dichtel; Aaron I. Packman (Water Research, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

The potent human CAR activator CITCO is a non-genotoxic hepatic tumour-promoting agent in humanised constitutive androstane receptor mice but not in wild-type animals - C. J. Henderson; A. W. McLaren; A. K. MacLeod; D. Lin; A. R. Cameron; L. R. Chatham; J. Moggs; F. Inesta-Vaquera; John P. Thomson; Richard R. Meehan; P. Chakravarty; M. Schwarz; et al. (Archives of Toxicology, 2025)
A large number of drugs and compounds produced by the chemical and agrochemical industry, often referred to as ‘non-genotoxic carcinogens’ (NGC), score as tumour promotors in rodent models. It is unclear whether these compounds act similarly in humans. The most extensively investigated compounds have been the anti-convulsive drugs, phenobarbital (PB), and phenytoin. Liver tumours induced by PB are dependent upon the activation of the constitutive androstane receptor (CAR). However, marked species differences in CAR activation by exogenous chemicals exist with some being much more potent activators of human CAR, e.g., 6-(4-chlorophenyl)imidazo[2,1-β][1,3]thiazole-5-carbaldehyde-O-(3,4-dichlorobenzyl)oxime (CITCO). We have compared CITCO-induced tumour formation in the livers of mice in which murine CAR has been replaced with its human counterpart. Our findings reveal that CITCO-dependent liver tumours are only formed in mice-expressing human CAR and not in wild-type animals. In addition, contrary to one of the proposed mechanisms of NGC carcinogenicity, we show that CITCO did not induce a hyperplastic response in the liver of the humanised mice. These data raise some key questions about the mechanism of action of NGCs and identify the limitations of current rodent carcinogenicity test systems in relation to risk assessment.

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Analysis of Increased False-Positive ELISA Results for HIV in the Blood of Donors Infected with SARS-CoV-2 - H. Lin; Z. Wang; Q. Ren; Z. Cai; F. Ge; W. Yuan; T. Liao; Y. Wu; R. Peng; Y. Gu; Y. Kuang (Bulletin of Experimental Biology and Medicine, 2025)

Reversal of practical resistance in fall armyworm to Cry1F maize: a case report on the resistance to susceptibility in Bt crops from the southeastern USA - Tiago Silva; Gregory A. Sword; Andie Miller; Jawwad A. Qureshi; Graham P. Head; Dawson D. Kerns; Juan Luis Jurat-Fuentes; James Villegas; Tyler B. Towles; Xinzhi Ni; Francis P. F. Reay-Jones; Daniel Carrillo; et al. (Journal of Pest Science, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Prenatal blood metals, per- and polyfluoroalkyl substances and antigen- or mitogen-stimulated cord blood lymphocyte proliferation and cytokine secretion - Anna R. Smith; Pi-I.D. Lin; Sheryl L. Rifas-Shiman; Abby F. Fleisch; Robert O. Wright; Brent Coull; Patricia W. Finn; Emily Oken; Diane R. Gold; Andres Cardenas (Environmental Research, 2024)

A methodology for gene level omics-WAS integration identifies genes influencing traits associated with cardiovascular risks: the Long Life Family Study - Sandeep Acharya; Shu Liao; Wooseok J. Jung; Yu S. Kang; Vaha Akbary Moghaddam; Mary F. Feitosa; Mary K. Wojczynski; Shiow Lin; Jason A. Anema; Karen Schwander; Jeff O. Connell; Michael A. Province; et al. (Human Genetics, 2024)
The Long Life Family Study (LLFS) enrolled 4953 participants in 539 pedigrees displaying exceptional longevity. To identify genetic mechanisms that affect cardiovascular risks in the LLFS population, we developed a multi-omics integration pipeline and applied it to 11 traits associated with cardiovascular risks. Using our pipeline, we aggregated gene-level statistics from rare-variant analysis, GWAS, and gene expression-trait association by Correlated Meta-Analysis (CMA). Across all traits, CMA identified 64 significant genes after Bonferroni correction (p ≤ 2.8 × 10 –7 ), 29 of which replicated in the Framingham Heart Study (FHS) cohort. Notably, 20 of the 29 replicated genes do not have a previously known trait-associated variant in the GWAS Catalog within 50 kb. Thirteen modules in Protein–Protein Interaction (PPI) networks are significantly enriched in genes with low meta-analysis p-values for at least one trait, three of which are replicated in the FHS cohort. The functional annotation of genes in these modules showed a significant over-representation of trait-related biological processes including sterol transport, protein-lipid complex remodeling, and immune response regulation. Among major findings, our results suggest a role of triglyceride-associated and mast-cell functional genes FCER1A , MS4A2 , GATA2 , HDC , and HRH4 in atherosclerosis risks. Our findings also suggest that lower expression of ATG2A , a gene we found to be associated with BMI, may be both a cause and consequence of obesity. Finally, our results suggest that ENPP3 may play an intermediary role in triglyceride-induced inflammation. Our pipeline is freely available and implemented in the Nextflow workflow language, making it easily runnable on any compute platform ( https://nf-co.re/omicsgenetraitassociation ) .

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Vegetation−fire feedbacks increase subtropical wildfire risk in scrubland and reduce it in forests - P. Wei; B. Lamont; T. He; W. Xue; P.C. Wang; W. Song; R. Zhang; A.B. Keyhani; S. Zhao; W. Lu; F. Dong; R. Gao; et al. (Journal of Environmental Management, 2024)

Sustainability assessment and pathways for U.S. domestic paper recycling - Enze Jin; Stijn van Ewijk; Koichi S. Kanaoka; Yohannes A. Alamerew; Hui Lin; Zhi Cao; Banafsheh Jabarivelisdeh; Kornel F. Ehmann; Marian R. Chertow; Eric Masanet (Resources, Conservation and Recycling, 2023)

The Pacific water flow branches in the eastern Chukchi Sea - Robert S. Pickart; Peigen Lin; Frank Bahr; Leah T. McRaven; Jie Huang; Astrid Pacini; Kevin R. Arrigo; Carin J. Ashjian; Catherine Berchok; Mark F. Baumgartner; Kyoung-Ho Cho; Lee W. Cooper; et al. (Progress in Oceanography, 2023)

Migraine, chronic kidney disease and kidney function: observational and genetic analyses - Wenqiang Zhang; Li Zhang; Luo Yang; Chenghan Xiao; Xueyao Wu; Peijing Yan; Huijie Cui; Chao Yang; Jingwei Zhu; Xuan Wu; Mingshuang Tang; Yutong Wang; et al. (Human Genetics, 2023)
Epidemiological studies demonstrate an association between migraine and chronic kidney disease (CKD), while the genetic basis underlying the phenotypic association has not been investigated. We aimed to help avoid unnecessary interventions in individuals with migraine through the investigation of phenotypic and genetic relationships underlying migraine, CKD, and kidney function. We first evaluated phenotypic associations using observational data from UK Biobank ( N = 255,896). We then investigated genetic relationships leveraging genomic data in European ancestry for migraine ( N case / N control = 48,975/540,381), CKD ( N case / N control = 41,395/439,303), and two traits of kidney function (estimated glomerular filtration rate [eGFR, N = 567,460] and urinary albumin-to-creatinine ratio [UACR, N = 547,361]). Observational analyses suggested no significant association of migraine with the risk of CKD (HR = 1.13, 95% CI = 0.85–1.50). While we did not find any global genetic correlation in general, we identified four specific genomic regions showing significant for migraine with eGFR. Cross-trait meta-analysis identified one candidate causal variant (rs1047891) underlying migraine, CKD, and kidney function. Transcriptome-wide association study detected 28 shared expression–trait associations between migraine and kidney function. Mendelian randomization analysis suggested no causal effect of migraine on CKD (OR = 1.03, 95% CI = 0.98–1.09; P = 0.28). Despite a putative causal effect of migraine on an increased level of UACR (log-scale-beta = 0.02, 95% CI = 0.01–0.04; P = 1.92 × 10 −3 ), it attenuated to null when accounting for both correlated and uncorrelated pleiotropy. Our work does not find evidence supporting a causal association between migraine and CKD. However, our study highlights significant biological pleiotropy between migraine and kidney function. The value of a migraine prophylactic treatment for reducing future CKD in people with migraine is likely limited.

Interactions between marine megafauna and plastic pollution in Southeast Asia - Lucy C.M. Omeyer; Emily M. Duncan; Neil Angelo S. Abreo; Jo Marie V. Acebes; Lea A. AngSinco-Jimenez; Sabiqah T. Anuar; Lemnuel V. Aragones; Gonzalo Araujo; Luis R. Carrasco; Marcus A.H. Chua; Muhammad R. Cordova; Lantun P. Dewanti; et al. (Science of The Total Environment, 2023)

A systematic evidence map for the evaluation of noncancer health effects and exposures to polychlorinated biphenyl mixtures - Laura M. Carlson; Krista Christensen; Sharon K. Sagiv; Pradeep Rajan; Carolyn R. Klocke; Pamela J. Lein; Evan Coffman; Rachel M. Shaffer; Erin E. Yost; Xabier Arzuaga; Pam Factor-Litvak; Alexander Sergeev; et al. (Environmental Research, 2023)

Tallo: A global tree allometry and crown architecture database - Tommaso Jucker; Fabian Jörg Fischer; Jérôme Chave; David A. Coomes; John Caspersen; Arshad Ali; Grace Jopaul Loubota Panzou; Ted R. Feldpausch; Daniel Falster; Vladimir A. Usoltsev; Stephen Adu‐Bredu; Luciana F. Alves; et al. (Global Change Biology, 2022)
Data capturing multiple axes of tree size and shape, such as a tree's stem diameter, height and crown size, underpin a wide range of ecological research—from developing and testing theory on forest structure and dynamics, to estimating forest carbon stocks and their uncertainties, and integrating remote sensing imagery into forest monitoring programmes. However, these data can be surprisingly hard to come by, particularly for certain regions of the world and for specific taxonomic groups, posing a real barrier to progress in these fields. To overcome this challenge, we developed the Tallo database, a collection of 498,838 georeferenced and taxonomically standardized records of individual trees for which stem diameter, height and/or crown radius have been measured. These data were collected at 61,856 globally distributed sites, spanning all major forested and non‐forested biomes. The majority of trees in the database are identified to species (88%), and collectively Tallo includes data for 5163 species distributed across 1453 genera and 187 plant families. The database is publicly archived under a CC‐BY 4.0 licence and can be access from: https://doi.org/10.5281/zenodo.6637599 . To demonstrate its value, here we present three case studies that highlight how the Tallo database can be used to address a range of theoretical and applied questions in ecology—from testing the predictions of metabolic scaling theory, to exploring the limits of tree allometric plasticity along environmental gradients and modelling global variation in maximum attainable tree height. In doing so, we provide a key resource for field ecologists, remote sensing researchers and the modelling community working together to better understand the role that trees play in regulating the terrestrial carbon cycle.

Extended Middle Cerebral Artery Occlusion (MCAO) Model to Mirror Stroke Patients Undergoing Thrombectomy - Sarah J. Messmer; Kathleen E. Salmeron; Jacqueline A. Frank; Christopher J. McLouth; Douglas E. Lukins; Tyler C. Hammond; Ai-Ling Lin; Justin F. Fraser; Keith R. Pennypacker (Translational Stroke Research, 2022)

Overall and central obesity and prostate cancer risk in African men - Ilir Agalliu; Wei-Kaung Jerry Lin; Janice S. Zhang; Judith S. Jacobson; Thomas E. Rohan; Ben Adusei; Nana Yaa F. Snyper; Caroline Andrews; Elkhansa Sidahmed; James E. Mensah; Richard Biritwum; Andrew A. Adjei; et al. (Cancer Causes & Control, 2022)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

A global collaboration to study intimate partner violence-related head trauma: The ENIGMA consortium IPV working group - Carrie Esopenko; Jessica Meyer; Elisabeth A. Wilde; Amy D. Marshall; David F. Tate; Alexander P. Lin; Inga K. Koerte; Kimberly B. Werner; Emily L. Dennis; Ashley L. Ware; Nicola L. de Souza; Deleene S. Menefee; et al. (Brain Imaging and Behavior, 2021)

The clinical utility of proton magnetic resonance spectroscopy in traumatic brain injury: recommendations from the ENIGMA MRS working group - Brenda L Bartnik-Olson; Jeffry R Alger; Talin Babikian; Ashley D Harris; Barbara Holshouser; Ivan I Kirov; Andrew A Maudsley; Paul M Thompson; Emily L Dennis; David F Tate; Elisabeth A Wilde; Alexander Lin (Brain Imaging and Behavior, 2021)

The ENIGMA sports injury working group:– an international collaboration to further our understanding of sport-related brain injury - Inga K. Koerte; Carrie Esopenko; Sidney R. Hinds; Martha E. Shenton; Elena M. Bonke; Jeffrey J. Bazarian; Kevin C. Bickart; Erin D. Bigler; Sylvain Bouix; Thomas A. Buckley; Meeryo C. Choe; Paul S. Echlin; et al. (Brain Imaging and Behavior, 2021)
Sport-related brain injury is very common, and the potential long-term effects include a wide range of neurological and psychiatric symptoms, and potentially neurodegeneration. Around the globe, researchers are conducting neuroimaging studies on primarily homogenous samples of athletes. However, neuroimaging studies are expensive and time consuming, and thus current findings from studies of sport-related brain injury are often limited by small sample sizes. Further, current studies apply a variety of neuroimaging techniques and analysis tools which limit comparability among studies. The ENIGMA Sports Injury working group aims to provide a platform for data sharing and collaborative data analysis thereby leveraging existing data and expertise. By harmonizing data from a large number of studies from around the globe, we will work towards reproducibility of previously published findings and towards addressing important research questions with regard to diagnosis, prognosis, and efficacy of treatment for sport-related brain injury. Moreover, the ENIGMA Sports Injury working group is committed to providing recommendations for future prospective data acquisition to enhance data quality and scientific rigor.

Characterization and validation of QTLs for adult plant stripe rust resistance in Chinese wheat landrace Dabaimai - M. Y. Wang; M. R. Xu; F. T. Wang; S. J. A. Shah; J. Feng; R. M. Lin; S. C. Xu (Cereal Research Communications, 2021)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

A System Level Analysis of Coastal Ecosystem Responses to Hurricane Impacts - C. J. Patrick; L. Yeager; A. R. Armitage; F. Carvallo; V. M. Congdon; K. H. Dunton; M. Fisher; A. K. Hardison; J. D. Hogan; J. Hosen; X. Hu; B. Kiel Reese; et al. (Estuaries and Coasts, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Global Perspectives on Observing Ocean Boundary Current Systems - Robert E. Todd; Francisco P. Chavez; Sophie Clayton; Sophie Cravatte; Marlos Goes; Michelle Graco; Xiaopei Lin; Janet Sprintall; Nathalie V. Zilberman; Matthew Archer; Javier Arístegui; Magdalena Balmaseda; et al. (Frontiers in Marine Science, 2019)

Ocean Observations in Support of Studies and Forecasts of Tropical and Extratropical Cyclones - Ricardo Domingues; Akira Kuwano-Yoshida; Patricia Chardon-Maldonado; Robert E. Todd; George Halliwell; Hyun-Sook Kim; I.-I. Lin; Katsufumi Sato; Tomoko Narazaki; Lynn K. Shay; Travis Miles; Scott Glenn; et al. (Frontiers in Marine Science, 2019)

Taxonomy of the order Mononegavirales: update 2019 - Gaya K. Amarasinghe; María A. Ayllón; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Kim R. Blasdell; Thomas Briese; Paul A. Brown; Alexander Bukreyev; Anne Balkema-Buschmann; Ursula J. Buchholz; Camila Chabi-Jesus; et al. (Archives of Virology, 2019)

Taxonomy of the order Mononegavirales: second update 2018 - Piet Maes; Gaya K. Amarasinghe; María A. Ayllón; Christopher F. Basler; Sina Bavari; Kim R. Blasdell; Thomas Briese; Paul A. Brown; Alexander Bukreyev; Anne Balkema-Buschmann; Ursula J. Buchholz; Kartik Chandran; et al. (Archives of Virology, 2019)

Genomic signatures of experimental adaptive radiation in Drosophila - Pawel Michalak; Lin Kang; Mads F. Schou; Harold R. Garner; Volker Loeschcke (Molecular Ecology, 2019)
Abiotic environmental factors play a fundamental role in determining the distribution, abundance and adaptive diversification of species. Empowered by new technologies enabling rapid and increasingly accurate examination of genomic variation in populations, researchers may gain new insights into the genomic background of adaptive radiation and stress resistance. We investigated genomic variation across generations of large‐scale experimental selection regimes originating from a single founder population of Drosophila melanogaster , diverging in response to ecologically relevant environmental stressors: heat shock, heat knock down, cold shock, desiccation and starvation. When compared to the founder population, and to parallel unselected controls, there were more than 100,000 single nucleotide polymorphisms ( SNP s) displaying consistent allelic changes in response to selective pressures across generations. These SNP s were found in both coding and noncoding sequences, with the highest density in promoter regions, and involved a broad range of functionalities, including molecular chaperoning by heat‐shock proteins. The SNP patterns were highly stressor‐specific despite considerable variation among line replicates within each selection regime, as reflected by a principal component analysis, and co‐occurred with selective sweep regions. Only ~15% of SNP s with putatively adaptive changes were shared by at least two selective regimes, while less than 1% of SNP s diverged in opposite directions. Divergent stressors driving evolution in the experimental system of adaptive radiation left distinct genomic signatures, most pronounced in starvation and heat‐shock selection regimes.

Taxonomy of the order Mononegavirales: update 2018 - Gaya K. Amarasinghe; Nidia G. Aréchiga Ceballos; Ashley C. Banyard; Christopher F. Basler; Sina Bavari; Andrew J. Bennett; Kim R. Blasdell; Thomas Briese; Alexander Bukreyev; Yíngyún Caì; Charles H. Calisher; Cristine Campos Lawson; et al. (Archives of Virology, 2018)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Burly1 is a mouse QTL for lean body mass that maps to a 0.8-Mb region of chromosome 2 - Cailu Lin; Brad D. Fesi; Michael Marquis; Natalia P. Bosak; Anna Lysenko; Mohammed Amin Koshnevisan; Fujiko F. Duke; Maria L. Theodorides; Theodore M. Nelson; Amanda H. McDaniel; Mauricio Avigdor; Charles J. Arayata; et al. (Mammalian Genome, 2018)

Global environmental costs of China's thirst for milk - Zhaohai Bai; Michael R. F. Lee; Lin Ma; Stewart Ledgard; Oene Oenema; Gerard L. Velthof; Wenqi Ma; Mengchu Guo; Zhanqing Zhao; Sha Wei; Shengli Li; Xia Liu; et al. (Global Change Biology, 2018)
China has an ever‐increasing thirst for milk, with a predicted 3.2‐fold increase in demand by 2050 compared to the production level in 2010. What are the environmental implications of meeting this demand, and what is the preferred pathway? We addressed these questions by using a nexus approach, to examine the interdependencies of increasing milk consumption in China by 2050 and its global impacts, under different scenarios of domestic milk production and importation. Meeting China's milk demand in a business as usual scenario will increase global dairy‐related (China and the leading milk exporting regions) greenhouse gas ( GHG ) emissions by 35% (from 565 to 764 Tg CO 2eq ) and land use for dairy feed production by 32% (from 84 to 111 million ha) compared to 2010, while reactive nitrogen losses from the dairy sector will increase by 48% (from 3.6 to 5.4 Tg nitrogen). Producing all additional milk in China with current technology will greatly increase animal feed import; from 1.9 to 8.5 Tg for concentrates and from 1.0 to 6.2 Tg for forage (alfalfa). In addition, it will increase domestic dairy related GHG emissions by 2.2 times compared to 2010 levels. Importing the extra milk will transfer the environmental burden from China to milk exporting countries; current dairy exporting countries may be unable to produce all additional milk due to physical limitations or environmental preferences/legislation. For example, the farmland area for cattle‐feed production in New Zealand would have to increase by more than 57% (1.3 million ha) and that in Europe by more than 39% (15 million ha), while GHG emissions and nitrogen losses would increase roughly proportionally with the increase of farmland in both regions. We propose that a more sustainable dairy future will rely on high milk demanding regions (such as China) improving their domestic milk and feed production efficiencies up to the level of leading milk producing countries. This will decrease the global dairy related GHG emissions and land use by 12% (90 Tg CO 2eq reduction) and 30% (34 million ha land reduction) compared to the business as usual scenario, respectively. However, this still represents an increase in total GHG emissions of 19% whereas land use will decrease by 8% when compared with 2010 levels, respectively.

Formation and characteristics of the Xiaoba landslide in Fuquan, Guizhou, China - F. Lin; L. Z. Wu; R. Q. Huang; H. Zhang (Landslides, 2018)

Molecular screening of multidrug-resistance tuberculosis by a designated public health laboratory in Taiwan - H.-C. Lin; C.-L. Perng; Y.-W. Lai; F.-G. Lin; C.-J. Chiang; H.-A. Lin; R. Jou; T.-S. Chiueh (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Taxonomy of the order Mononegavirales: update 2017 - Gaya K. Amarasinghe; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Martin Beer; Nicolás Bejerman; Kim R. Blasdell; Alisa Bochnowski; Thomas Briese; Alexander Bukreyev; Charles H. Calisher; Kartik Chandran; et al. (Archives of Virology, 2017)

Development of In situ hybridization and real‐time PCR assays for the detection of Hepatospora eriocheir , a microsporidian pathogen in the Chinese mitten crab Eriocheir sinensis - Z F Ding; J Q Chen; J Lin; X S Zhu; G H Xu; R L Wang; Q G Meng; W Wang (Journal of Fish Diseases, 2017)
A microsporidian parasite, Hepatospora eriocheir , is an emerging pathogen for the Chinese mitten crab Eriocheir sinensis . Currently, there is scant information about the way it transmits infection in the crustacean of commercial importance, including its pathogenesis, propagation and infection route in vivo . In this study, chromogenic in situ hybridization ( ISH ) and quantitative real‐time PCR ( qPCR ) assays were developed to address this pressing need, and we provided an advance in the detection methods available. Pathogens can be seen in situ with associated lesions using ISH . Positive hybridization signals were noted inside the epithelial cells of the hepatopancreas, and putative free parasite spores were observed within the tubule lumen, which were associated with lesions detected by electron microscopy and haematoxylin and eosin (H&E) analysis. qPCR allows the determination of parasite loads in infected tissues, which is important for understanding disease progression and transmission. The hepatopancreas displayed the biggest statistical copy numbers among different tissues of infected crabs, confirming a tissue‐specific pathogen infection characteristic. The qPCR assay also proved to be suitable for the diagnosis of asymptomatic carrier crabs. Combination of the two methods could facilitate the study of H. eriocheir infection mechanism in E. sinensis , enhance the early diagnosis of the pathogen and improve the management of microsporidian diseases in commercial crustaceans.

Selective Isolation of a Eucalyptus spp. Woodchip Bacterial Community and Its Taxonomic and Metabolic Profiling - C. F. Nnadozie; J. Lin; R. Govinden (BioEnergy Research, 2017)

Identification of diverse bacterial communities for potential bio-aids capable of troubleshooting for wastewater biological treatment processes - H-W Kuo; C-Y Huang; C-N Chang; P-L Lee; Y-W Chen; C-F Huang; H-H Chang; Y-H Tang; S-Z Zeng; G-Y Li; C-R Lin; L-Z Chen (International Journal of Environmental Science and Technology, 2017)

Taxonomy of the order Mononegavirales: update 2016 - Claudio L. Afonso; Gaya K. Amarasinghe; Krisztián Bányai; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Nicolás Bejerman; Kim R. Blasdell; François-Xavier Briand; Thomas Briese; Alexander Bukreyev; Charles H. Calisher; et al. (Archives of Virology, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Epidemiology and characteristics of the dengue outbreak in Guangdong, Southern China, in 2014 - L. Huang; X. Luo; J. Shao; H. Yan; Y. Qiu; P. Ke; W. Zheng; B. Xu; W. Li; D. Sun; D. Cao; C. Chen; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

A Role for Low Density Lipoprotein Receptor-Related Protein 1 in the Cellular Uptake of Tissue Plasminogen Activator in the Lungs - Swan Lin; Jennifer Racz; Melissa F. Tai; Kristina M. Brooks; Phillip Rzeczycki; Lauren J. Heath; Michael W. Newstead; Theodore J. Standiford; Gus R. Rosania; Kathleen A. Stringer (Pharmaceutical Research, 2016)

Advanced neuroimaging applied to veterans and service personnel with traumatic brain injury: state of the art and potential benefits - Elisabeth A. Wilde; Sylvain Bouix; David F. Tate; Alexander P. Lin; Mary R. Newsome; Brian A. Taylor; James R. Stone; James Montier; Samuel E. Gandy; Brian Biekman; Martha E. Shenton; Gerald York (Brain Imaging and Behavior, 2015)

Hyperglycemia down-regulates cGMP-dependent protein kinase I expression in first trimester cytotrophoblast cells - Tammy Nguyen; Saunders Lin; Ahmed F. Pantho; Belinda M. Kohl-Thomas; Madhava R. Beeram; David C. Zawieja; Thomas J. Kuehl; M. Nasir Uddin (Molecular and Cellular Biochemistry, 2015)

AdeRS combination codes differentiate the response to efflux pump inhibitors in tigecycline-resistant isolates of extensively drug-resistant Acinetobacter baumannii - J.-R. Sun; C.-L. Perng; J.-C. Lin; Y.-S. Yang; M.-C. Chan; T.-Y. Chang; F.-M. Lin; T.-S. Chiueh (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Trends in the susceptibility of commonly encountered clinically significant anaerobes and susceptibilities of blood isolates of anaerobes to 16 antimicrobial agents, including fidaxomicin and rifaximin, 2008–2012, northern Taiwan - F. D. Wang; C. H. Liao; Y. T. Lin; W. H. Sheng; P. R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Characterization, tissue distribution and regulation of neuropeptideY in Schizothorax prenanti - R. Wei; C. Zhou; D. Yuan; T. Wang; F. Lin; H. Chen; H. Wu; Z. Xin; S. Yang; Y. Wang; D. Chen; J. Liu; et al. (Journal of Fish Biology, 2014)
In this study, the full‐length neuropeptide Y ( npy ) complementary (c) DNA was cloned in ya fish Schizothorax prenanti . npy cDNA was composed of 789 nucleotides with a 288 nucleotide open reading frame encoding a protein of 96 amino acids. The deduced amino acid sequences contained a 28 amino acids signal peptide followed by a 36 amino acids mature neuropeptide Y (NPY). The npy mRNA was expressed mainly in the brain and eye as detected by real‐time quantitative polymerase chain reaction RT‐PCR ( rt‐qPCR ). The S. prenanti NPY was detectable from blastulation to hatch, suggesting that npy might be involved in the late embryonic development of S. prenanti . An experiment was conducted to determine the expression profile of npy during feeding of a single meal and during long‐term fasting. The expression level of npy in fed fish was significantly decreased at 0·5, 1·5, 3 and 9 h post‐feeding (hpf) than in fasting fish. Fasting for 14 days induced an increase in npy messenger (m) RNA expression in the brain. Overall, the results suggest that NPY is a conserved peptide that might be involved in the regulation of feeding and other physiological function in S. prenanti .

Characterization of Schizothorax prenanti cgnrhII gene: fasting affects cgnrhII expression - T. Wang; D. Yuan; C. Zhou; F. Lin; H. Chen; H. Wu; R. Wei; Z. Xin; J. Liu; Y. Gao; D. Chen; S. Yang; et al. (Journal of Fish Biology, 2014)
In this study, the role of chicken gonadotropin‐releasing hormone II ( cgnrhII ) in feeding regulation was investigated in Schizothorax prenanti . First, the full‐length S. prenanti cgnrhII cDNA consisted of 693 bp with an open reading frame of 261 bp encoding a protein of 86 amino acids. Next, cgnrhII was widely expressed in the central and peripheral tissues. Last, there were significant changes in cgnrhII mRNA expression in the fasted group compared to the fed group in the S. prenanti hypothalamus during 24 h fasting ( P cgnrhII gene expression presented a significant decrease in the fasted group compared with the fed group ( P cgnrhII mRNA expression level between refed and fed group on day 9 ( P > 0·05). Thus, the results suggest that cGnRH II expression is influenced by fasting and the gene may be involved in feeding regulation in S. prenanti.

Isolation and molecular analysis of genes Stpk-V2 and Stpk-V3 homologous to powdery mildew resistance gene Stpk-V in a Dasypyrum villosum accession and its derivatives - Z. S. Lin; Y. L. Zhang; M. J. Wang; J. R. Li; K. Wang; X. Chen; Q. F. Xu; X. S. Zhang; X. G. Ye (Journal of Applied Genetics, 2013)

Warming up to climate change: a participatory approach to engaging with agricultural stakeholders in the Southeast US - Wendy-Lin Bartels; Carrie A. Furman; David C. Diehl; Fred S. Royce; Daniel R. Dourte; Brenda V. Ortiz; David F. Zierden; Tracy A. Irani; Clyde W. Fraisse; James W. Jones (Regional Environmental Change, 2013)

Phosphorus availability and rice grain yield in a paddy soil in response to long-term fertilization - Z. M. Lan; X. J. Lin; F. Wang; H. Zhang; C. R. Chen (Biology and Fertility of Soils, 2012)

A review of magnetic resonance imaging and diffusion tensor imaging findings in mild traumatic brain injury - M. E. Shenton; H. M. Hamoda; J. S. Schneiderman; S. Bouix; O. Pasternak; Y. Rathi; M.-A. Vu; M. P. Purohit; K. Helmer; I. Koerte; A. P. Lin; C.-F. Westin; et al. (Brain Imaging and Behavior, 2012)

Multi-Decadal Changes in Tundra Environments and Ecosystems: Synthesis of the International Polar Year-Back to the Future Project (IPY-BTF) - Terry V. Callaghan; Craig E. Tweedie; Jonas Åkerman; Christopher Andrews; Johan Bergstedt; Malcolm G. Butler; Torben R. Christensen; Dorothy Cooley; Ulrika Dahlberg; Ryan K. Danby; Fred J. A. Daniёls; Johannes G. de Molenaar; et al. (Ambio, 2011)

Seroprevalence of Mycoplasma hyopneumoniae in pigs in subtropical southern China - Y. He; M. J. Xu; D. H. Zhou; F. C. Zou; R. Q. Lin; C. C. Yin; X. H. He; R. Liang; M. Liang; X. Q. Zhu (Tropical Animal Health and Production, 2011)

Inheritance of stripe rust resistance to predominant Chinese races in six spring wheat cultivars from the pacific Northwest of the United States - Y. Gao; Q. Sun; R. Wang; J. Feng; F. Lin; N. Cui; X. Chen; S. Xu; Y. Bai; X. Xu (Cereal Research Communications, 2011)

Suprachoroidal Drug Delivery to the Back of the Eye Using Hollow Microneedles - Samirkumar R. Patel; Angela S. P. Lin; Henry F. Edelhauser; Mark R. Prausnitz (Pharmaceutical Research, 2011)

The detection of “Candidatus Mycoplasma haemobos” in cattle and buffalo in China - Q. L. Su; H. Q. Song; R. Q. Lin; Z. G. Yuan; J. F. Yang; G. H. Zhao; W. Y. Huang; Xing Quan Zhu (Tropical Animal Health and Production, 2010)

Antibacterial effect of electrolysed acid water on the nasal discharge from patients with chronic rhinosinusitis - R.-S. Jiang; S.-H. Wu; K.-L. Liang; J.-F. Lin; M.-C. Su; W.-K. Chen; F.-J. Lu (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

In vitro activities of doripenem and other carbapenems against clinically important bacteria isolated in intensive care units: nationwide data from the SMART Programme - S.-S. Jean; P.-R. Hsueh; W.-S. Lee; H.-T. Chang; M.-Y. Chou; I.-S. Chen; J.-H. Wang; C.-F. Lin; J.-M. Shyr; W.-C. Ko; J.-J. Wu; Y.-C. Liu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Intercomparison, interpretation, and assessment of spring phenology in North America estimated from remote sensing for 1982–2006 - MICHAEL A. WHITE; KIRSTEN M. De BEURS; KAMEL DIDAN; DAVID W. INOUYE; ANDREW D. RICHARDSON; OLAF P. JENSEN; JOHN O'KEEFE; GONG ZHANG; RAMAKRISHNA R. NEMANI; WILLEM J. D. Van LEEUWEN; JESSLYN F. BROWN; ALLARD De WIT; et al. (Global Change Biology, 2009)
Shifts in the timing of spring phenology are a central feature of global change research. Long‐term observations of plant phenology have been used to track vegetation responses to climate variability but are often limited to particular species and locations and may not represent synoptic patterns. Satellite remote sensing is instead used for continental to global monitoring. Although numerous methods exist to extract phenological timing, in particular start‐of‐spring (SOS), from time series of reflectance data, a comprehensive intercomparison and interpretation of SOS methods has not been conducted. Here, we assess 10 SOS methods for North America between 1982 and 2006. The techniques include consistent inputs from the 8 km Global Inventory Modeling and Mapping Studies Advanced Very High Resolution Radiometer NDVIg dataset, independent data for snow cover, soil thaw, lake ice dynamics, spring streamflow timing, over 16 000 individual measurements of ground‐based phenology, and two temperature‐driven models of spring phenology. Compared with an ensemble of the 10 SOS methods, we found that individual methods differed in average day‐of‐year estimates by ±60 days and in standard deviation by ±20 days. The ability of the satellite methods to retrieve SOS estimates was highest in northern latitudes and lowest in arid, tropical, and Mediterranean ecoregions. The ordinal rank of SOS methods varied geographically, as did the relationships between SOS estimates and the cryospheric/hydrologic metrics. Compared with ground observations, SOS estimates were more related to the first leaf and first flowers expanding phenological stages. We found no evidence for time trends in spring arrival from ground‐ or model‐based data; using an ensemble estimate from two methods that were more closely related to ground observations than other methods, SOS trends could be detected for only 12% of North America and were divided between trends towards both earlier and later spring.

Nationwide surveillance of antimicrobial resistance among Haemophilus influenzae and Streptococcus pneumoniae in intensive care units in Taiwan - S.-S. Jean; P.-R. Hsueh; W.-S. Lee; H.-T. Chang; M.-Y. Chou; I.-S. Chen; J.-H. Wang; C.-F. Lin; J.-M. Shyr; W.-C. Ko; J.-J. Wu; Y.-C. Liu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

The occurrence of the feline “Candidatus Mycoplasma haemominutum” in dog in China confirmed by sequence-based analysis of ribosomal DNA - Q. J. Zhuang; H. J. Zhang; R. Q. Lin; M. F. Sun; X. J. Liang; X. W. Qin; W. J. Pu; X. Q. Zhu (Tropical Animal Health and Production, 2009)

Prevalence of helminths in water buffaloes in Hunan Province, China - Y. Liu; F. Li; W. Liu; R. S. Dai; Y. M. Tan; D. S. He; R. Q. Lin; X. Q. Zhu (Tropical Animal Health and Production, 2009)

Nationwide surveillance of antimicrobial resistance among Enterobacteriaceae in intensive care units in Taiwan - S.-S. Jean; P.-R. Hsueh; W.-S. Lee; H.-T. Chang; M.-Y. Chou; I.-S. Chen; J.-H. Wang; C.-F. Lin; J.-M. Shyr; W.-C. Ko; J.-J. Wu; Y.-C. Liu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

Selective Contrast Enhancement of Individual Alzheimer’s Disease Amyloid Plaques Using a Polyamine and Gd-DOTA Conjugated Antibody Fragment Against Fibrillar Aβ42 for Magnetic Resonance Molecular Imaging - Muthu Ramakrishnan; Thomas M. Wengenack; Karunya K. Kandimalla; Geoffry L. Curran; Emily J. Gilles; Marina Ramirez-Alvarado; Joseph Lin; Michael Garwood; Clifford R. Jack Jr.; Joseph F. Poduslo (Pharmaceutical Research, 2008)

Ethmoid sinus mycology of chronic rhinosinusitis - R. S. Jiang; K. L. Liang; J. Y. Shiao; J. F. Lin; M. C. Su; C. H. Hsin; F. J. Lu (European Journal of Clinical Microbiology & Infectious Diseases, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Seismo-Geochemical Variations in SW Taiwan: Multi-Parameter Automatic Gas Monitoring Results - T. F. Yang; C.-C. Fu; V. Walia; C.-H. Chen; L. L. Chyi; T.-K. Liu; S.-R. Song; M. Lee; C.-W. Lin; C.-C. Lin (Pure and Applied Geophysics, 2006)

The Complete Mitochondrial Genome Sequence and Characterization of Single-Nucleotide Polymorphisms in the Control Region of the Asian Seabass (Lates calcarifer) - G. Lin; L. C. Lo; Z. Y. Zhu; F. Feng; R. Chou; G. H. Yue (Marine Biotechnology, 2006)

Cloning and characterization of leaf cDNAs that are differentially expressed between wheat hybrids and their parents - L. M. Wu; Z. F. Ni; F. R. Meng; Z. Lin; Q. X. Sun (Molecular Genetics and Genomics, 2003)

Gene content and organization of an 85-kb DNA segment from the genome of the phytopathogenic mollicute Spiroplasma kunkelii - Y. Zhao; R. W. Hammond; R. Jomantiene; E. L. Dally; I.-M. Lee; H. Jia; H. Wu; S. Lin; P. Zhang; S. Kenton; F. Z. Najar; A. Hua; et al. (Molecular Genetics and Genomics, 2003)

Photodegradation of Diesel Oil in Aqueous Solutions - P. Zhong; L. R. Kong; Z. F. Lin; G. M. Liu (Bulletin of Environmental Contamination and Toxicology, 2003)

Biological Monitoring of Environment Exposure to Safrole and the Taiwanese Betel Quid Chewing - M. J. W. Chang; C. Y. Ko; R. F. Lin; L. L. Hsieh (Archives of Environmental Contamination and Toxicology, 2002)

A genetic linkage map of Nicotiana plumbaginifolia/ Nicotiana longiflora based on RFLP and RAPD markers - T. Y. Lin; Y. Y. Kao; S. Lin; R. F. Lin; C. M. Chen; C. H. Huang; C. K. Wang; Y. Z. Lin; C. C. Chen (Theoretical and Applied Genetics, 2001)

Environmental Exposure to Polycyclic Aromatic Hydrocarbons and Total Suspended Particulates in a Taiwanese Temple - T-C. Lin; F-H. Chang; J-H. Hsieh; H-R. Chao; M-R. Chao (Bulletin of Environmental Contamination and Toxicology, 2001)

Molecular epidemiology of enterovirus 71 in Taiwan - P.-Y. Chu; K.-H. Lin; K.-P. Hwang; L.-C. Chou; C.-F. Wang; S.-R. Shih; J.-R. Wang; Y. Shimada; H. Ishiko (Archives of Virology, 2001)

Blood and Urine Cadmium Levels in Relation to Demographic and Life Style in Middle Aged and Elderly Men - Y. C. Chen; Y. S. Pu; R. S. Lin; C. Y. Yang; M. K. Lai; S. H. Liu; F.-C. Sung (Bulletin of Environmental Contamination and Toxicology, 2001)

Development of a plant regeneration system based on friable embryogenic callus in the ornamental Alstroemeria - H. -S. Lin; C. van der Toorn; K. J. J. M. Raemakers; R. G. F. Visser; M.J. De Jeu; E. Jacobsen (Plant Cell Reports, 2000)

Central and peripheral tissue distribution of diclofenac after subcutaneous injection in the rat - R. F. Grace; S. R. Edwards; L. E. Mather; Y. Lin; I. Power (Inflammopharmacology, 2000)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Symposia lectures - F. Parak; A. Ostermann; G. U. Nienhaus; Nobuo Niimura; William A. Eaton; Stephen J. Hagen; Eric R. Henry; James Hofrichter; Gouri Jas; Lisa Lapidus; Victor Muñoz; Chih-chen Wang; et al. (Journal of Biosciences, 1999)

Models of corundum origin from alkali basaltic terrains: a reappraisal - F. Lin Sutherland; Paul W. O. Hoskin; C. Mark Fanning; Robert R. Coenraads (Contributions to Mineralogy and Petrology, 1998)

Shade effects on forage crops with potential in temperate agroforestry practices - C. H. Lin; R. L. McGraw; M. F. George; H. E. Garrett (Agroforestry Systems, 1998)

RFLP mapping of QTLs conferring salt tolerance during germination in an interspecific cross of tomato - M. R. Foolad; F. Q. Chen; G. Y. Lin (Theoretical and Applied Genetics, 1998)

Chemical Ecology of Cottonwood Leaf Beetle Adult Feeding Preferences on Populus - S. Lin; B. F. Binder; E. R. Hart (Journal of Chemical Ecology, 1998)

Insect Feeding Stimulants from the Leaf Surface of Populus - S. Lin; B. F. Binder; E. R. Hart (Journal of Chemical Ecology, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

Assignment of DNA markers to Nicotiana sylvestris chromosomes using monosomic alien addition lines - D. F. Suen; C. K. Wang; R. F. Lin; Y. Y. Kao; F. M. Lee; C. C. Chen (Theoretical and Applied Genetics, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

Acute hepatotoxicity of a tetrachlorobiphenyl?Changes in the hepatocyte ultrastructure and plasma membrane-bound enzymes - F. S. Lin; M. T. Hsia; J. R. Allen (Archives of Environmental Contamination and Toxicology, 1979)